Europa (neu) erzählen Inszenierungen Europas in politischer, theologischer und kulturwissenschaftlicher Perspektive - Kirschner, Martin (Transformation transdisziplinär, 2022)
At a time of global crises, the understanding and role of Europe are being called into question. Reflecting on Europe requires reconsidering the meaning of modernity, our understanding of politics and the relation between faith and reason. Which narratives and what kind of performances constitute the public space in Europe? How can we overcome colonial and imperial logic when talking about 'Europe'? Based on reflections on performative political theology, this volume explores ways of and names criteria for (re-)narrating Europe. Its introduction takes the war in Ukraine into account.